Appropriating Shakespearean graphic novels for Malaysian classrooms to create correct gender representations - Ismail, Hanita Hanim; Azizan, Mazlin; Rashid, Radzuwan Ab; Asif, Muhammad (Frontiers in Psychology, 2022)
Public awareness on gender education may not be easily translated in living classrooms, which prompts new alternatives. In this study, we explored Shakespearean graphic novels in exposing Malaysian school students to gender-related issues. The two-fold research entails tracing the female presence in eight selected digital graphic novels that define the gender and places social expectations across the globe; and secondly, gathering teachers’ perception of these selected graphic novels. The chosen graphics were divided into two categories – those published as the cover pages of graphic novels and those that were contested for the Graphic Shakespeare Competition established in 2016. These stereotypical images of a woman are not in line to achieve inclusivity and correct gender representations. The data analysed based on a semi-structured interview on six ESL teachers suggests that as much as the graphic novels are seen as valuable in pedagogical contexts and in exposing the students to learning English and gender representations through literature, the material selection and pedagogical approaches, including determining the classroom activities must be cautiously considered in terms of their cultural appropriateness to ensure students’ readiness and effective outcomes. Discussing these pertinent issues, especially in addressing gender (mis)representations relevant to education, helps pave a new route within the UN SDG Goal 5 where gender nuances and phrases ought to be carefully constructed in a new narrative that shapes global perception towards women.